Homology-Directed Repair of a Defective Glabrous Gene in Arabidopsis With Cas9-Based Gene Targeting - Hahn, Florian; Eisenhut, Marion; Mantegazza, Otho; Weber, Andreas P. M. (Frontiers in Plant Science, 2018)
The CRISPR/Cas9 system has emerged as a powerful tool for targeted genome editing in plants and beyond. Double-strand breaks induced by the Cas9 enzyme are repaired by the cell’s own repair machinery either by the non-homologous end joining pathway or by homologous recombination. While the first repair mechanism results in random mutations at the double-strand break site, homologous recombination uses the genetic information from a highly homologous repair template as blueprint for repair of the break. By offering an artificial repair template, this pathway can be exploited to introduce specific changes at a site of choice in the genome. However, frequencies of double-strand break repair by homologous recombination are very low. In this study, we compared two methods that have been reported to enhance frequencies of homologous recombination in plants. The first method boosts the repair template availability through the formation of viral replicons, the second method makes use of an in planta gene targeting approach. Additionally, we comparatively applied a nickase instead of a nuclease for target strand priming. To allow easy, visual detection of homologous recombination events, we aimed at restoring trichome formation in a glabrous Arabidopsis mutant by repairing a defective glabrous1 gene. Using this efficient visual marker, we were able to regenerate plants repaired by homologous recombination at frequencies of 0.12% using the in planta gene targeting approach, while both approaches using viral replicons did not yield any trichome-bearing plants.